Three-dimensional convection regimes in a two-layer system with evaporation for different types of thermal loads on a substrate - Goncharova, Ol’ga Nikolayevna (Computational Continuum Mechanics, 2023)
A three-dimensional generalization of the Ostroumov–Birikh solution of the convection equations is constructed to model the two-layer flows with respect to diffusion evaporation (condensation) at the interface. An infinite rectangular channel filled with a liquid and a gas-vapor mixture that have a common interface is under the action of the longitudinal temperature gradient and the transversely directed gravity field. Both media are assumed to be the viscous heat-conducting incompressible fluids. On the basis of the exact solution of a special type, the characteristics of flows arising under conditions of a linearly distributed thermal load on the substrate and thermal insulation of the upper and lateral walls of the channel are studied. The three-dimensional solution structure dictates the reduction of the original problem to a set of two-dimensional formulations. The numerical solution of these problems, carried out on the basis of a longitudinal-transverse finite-difference scheme, makes it possible to describe real convective regimes. In order to determine the control mechanisms for the two-layer flows and to predict possible types of instability, the influence of the boundary thermal regime on the evaporative convection parameters is analyzed. Temperature drops in the system caused both by external thermal action and by evaporation processes lead to the formation of vortex structures of a complex symmetry the topology of which significantly depends on the intensity of thermal load, the type of liquid coolant, and the thickness of liquid layer. The characteristics of the two-layer flows of the working systems such as ethanol–nitrogen and HFE7100–nitrogen are investigated. Translational-rotational flows in the two-layer systems are realized in the form of convection rolls. Differences in the formation of longitudinal thermal rolls, a near-surface hot layer, cold thermocline and near-wall thermal rolls with defects are studied. The projections of fluid flow tubes and the trajectories of liquid particles, as well as the temperature and vapor concentration distributions, are presented.